Carbon footprint associated with a small-scale emissions reduction initiative for sustainable event management - V. de cadenet; P. Parinyakulset; W. Komkum; P. Boondaeng; P. Raksa (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: In today’s world, finding ways to reduce our carbon footprint and saving energy has become increasingly important. Simple energy-saving measures can not only reduce utility costs but also contribute to a healthier and more sustainable planet. In this study, the Suranaree Agricultural Fair 2025, a nine-day public event hosted by Suranaree University of Technology, located in Nakhon Ratchasima Province, Thailand, was selected as a representative case for examining the environmental impacts of large-scale academic gatherings. The event, promoting sustainable agricultural innovation and the Bio-Circular-Green Economy, was held across an area of 226,068.19 square meters and attended by 258,917 participants. The objective of this study was to assess the carbon footprint of the fair, identify major sources of greenhouse gas emissions, and propose opportunities for emission reduction.METHODS: A comprehensive carbon footprint assessment was conducted by evaluating emissions from travel, accommodation, food consumption, waste generation, electricity, and water usage. Data was collected through participant surveys, utility metering, and waste audits. Emissions were calculated using standard emission factors and presented in carbon dioxide equivalent values per person, per square meter, and per event hour.FINDINGS: The total carbon footprint of the event was estimated at 1,524,844.09 kilograms of carbon dioxide equivalent. This equates to 5.89 kilograms per person, 6.74 kilograms per square meters, and 14,115.19 kilograms per hour of the event. Food consumption and participant travel were the primary contributors, accounting for more than 67 percent of the total emissions. Emission patterns were also analyzed across different participant groups, revealing varying behaviors and engagement levels that influence carbon emission results.CONCLUSION: This study demonstrates the significant environmental impact of large-scale academic fairs and provides a foundational dataset for ongoing emissions monitoring. It offers targeted recommendations to enhance data collection, promote low-carbon practices, and support institutional efforts toward achieving carbon neutrality. These insights contribute to integrating sustainability principles into event management within the higher education sector.